FACTORS AFFECTING INTENTION TO VISIT HALAL TOURISM CITY: A SURVEY TO FIVE HALAL TOURISM DESTINATION IN INDONESIA - Julina Julina; Riduan Mas’ud; Desrir Miftah; Mahyarni Mahyarni; Fakhrurrozi Fakhrurrozi (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Tourism travel now has been a lifestyle of most community. Recently, halal tourism has received a lot of attention from various parties. The Indonesian government has determined several provinces as Halal tourism destination areas (Nusa Tenggara Barat (NTB), Nanggroe Aceh Darussalam (NAD), Sumatera Barat, DKI Jakarta, and Jawa Barat). This study attempts to examine the factors that influence the intention to visit that city. Data was collected using a questionnaire distributed using google form. The sampling technique used is purposive sampling. A total of 396 data are eligible for further analysis using SEM-AMOS. The results of the study found that the variables that influence attitudes and intentions to visit halal tourism vary between halal tourism areas. Variables that have a consistent effect are found in subjective norms where the results are positive and significant on attitudes and intentions. On the other hand, none of the halal tourism areas found a significant effect of PBC on intentions.